KONSEP PEMBANGUNAN EKONOMI PERSPEKTIF ISLAM - Djumadi Djumadi (TAHKIM, 2017)
Economic development is the Islamic perspective of human development as a whole not just the physical needs, but more of it is mental development-spiritual. The Islamic view on economic development is focused on (a) the mankind from extinction. (b) Human Resources (HR) good, reflecting Source Revenues Halal (SPH). (c) maintain and preserve natural ecosystems from damage; (d) the maximum utilization of the land and pay taxes to the state. Results show that the interpretation of the message of the Qur’an on the Islamic perspective of economic development has not received much attention, especially in predominantly Muslim countries. One indicator development are described, among others, levels of inequality and poverty that struck various NSB. Some of the solutions that need attention: (1) reduce routine expenditures, and increase the quantity Fislkal; (2) with establishment of economic development aimed at improving the quality of rural areas; (3) The availability of employment and human resource development of agriculture sector. Keywords: economic development, Islamic perspective